No Pain, No Gain: An Affect-Based Model of Developmental Job Experience and the Buffering Effects of Emotional Intelligence - Dong, Yuntao; Seo, Myeong-Gu; Bartol, Kathryn M. (Academy of Management Journal, 2014)
Drawing on an overarching framework of transactional stress theory, this study develops and tests an affect-based model of developmental job experience (DJE) that explicates the affective mechanisms through which DJE is associated with both positive and negative individual outcomes—advancement potential and turnover intention—and the buffering role of emotional intelligence (EI) in the affective processes. In a sample of 214 early-career managers, we found DJE to be related to increased advancement potential by boosting employees' pleasant feelings, but also that it can fail in this regard by increasing their unpleasant feelings. Moreover, whereas it is not surprising that there was a negative relationship between DJE and turnover intention mediated by pleasant feelings, our results also demonstrated a positive relationship via unpleasant feelings, depending on employees' levels of EI. Specifically, they suggested that DJE was positively related to turnover intention for only low-EI employees, but not for high-EI employees.